Do mergers and acquisitions create value?: The post-M&A performance of acquiring firms in China and India. Issue 2 (19th June 2019) - Reddy, Krishna; Qamar, Muhammad; Yahanpath, Noel
Abstract : Purpose: The purpose of this paper is to study whether mergers and acquisitions (M&As) create value in Indian and Chinese markets. Design/methodology/approach: The authors study abnormal returns (AR) created by the acquiring firms in Indian and Chinese markets relating to M&A announcements, using the following three different statistical methods: i.e. mean, market and ordinary least squares adjusted return models. Findings: On average, M&A announcements do not create value for the firms in Chinese and Indian economies. For the mean model, M&As create value for Chinese firms, whereas for the Indian firms no such value is created for the same event windows. The regression results showed that debt has a positive impact on the AR and cumulative average abnormal returns at 1, 5 and 10 per cent significance levels, respectively. Research limitations/implications: This study suggests increasing the sample size and period and using the instrumental variables regression to ensure the estimator's impartiality, consistency and efficiency. With the investigative period surrounding a financial crisis, the estimators may have omitted bias. Originality/value: Multiple methods used in this paper made it possible to capture the level of method variance in the AR, which is unusual in the Chinese and Indian context. Hence, the current study provides local knowledge and further strengthens the literature about M&As. The authors also regress AR with firm-specific factors, the consideration of which is scarce in the previous literature. Furthermore, much of what the authors know about M&A is relevant to developed economies.